Literature Review: Intervention for Sleep Problem on Preschooler - Eka Wahyuningrum (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2024)
Introduction: About 30% preschoolers in the world was experienced sleep problem. Sleep problem intervention is needed for promoting growth and developing children. Objectives:  To analyze the intervention for sleep problem in preschooler. Methods: This study uses systematic review design and conducted in Google scholar database. The search using keyword “Intervention and Sleep Problem and Preschool”. Population and setting of this study is preschooler in community services. Intervention of this study is sleep problem intervention for preschooler and outcome measure is sleep. Inclusion criteria for articles were published in journal with English or Indonesian language, between 2011 until 2020, article with quantitative design or systematic review, title of article relevant with topic. Review articles were excluded, as well as those including participants with hospitalization, do not include applicable intervention. Results:  A total of 15 studies were critical appraisal using tables that consist of information about sample, instrument, and type of intervention, result and conclusionin the review. Eight studies were targeting parents, two studies were targeting parents and preschooler and four studies were targeting preschooler. Most of intervention that applied to parents was sleep education about sleep hygiene that delivered directly, indirectly (internet), consultation, and modification of media use, Cognitive Behavioral Therapy (CBT), behavioral treatment and combined intervention. Duration of intervention is varies, most of study need time less than 1 month. Conclusions:  Sleep education about sleep hygiene for parents is recommended intervention to solve sleep problem according to family center care. There were limited studies targeting parents and children directly.